2013
DOI: 10.1099/ijs.0.047902-0
|View full text |Cite
|
Sign up to set email alerts
|

Nocardioides marinquilinus sp. nov., isolated from coastal seawater

Abstract: A Gram-stain-positive, non-motile, strictly aerobic, non-spore-forming and short rod-shaped bacterial strain, CL-GY44 T , was isolated from coastal seawater, Korea. Analysis of the 16S rRNA gene sequence of strain CL-GY44 T revealed a clear affiliation with the genus Nocardioides. Based on phylogenetic analysis, strain CL-GY44 T showed the closest phylogenetic relationship with Nocardioides ginsengagri BX5-10 T and Nocardioides plantarum NCIMB 12834 T . Strain CL-GY44 T was not able to grow in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…¡96.3 %) with recognized species of the genus Nocardioides and the phylogenetic position of strain PAMC 26527 T showed that the strain could be assigned to a novel species in the genus Nocardioides. The DNA G+C content of strain PAMC 26527 T was 69.3 mol%, within the range (67-75 mol%; Prauser, 1976;Yoon et al, 2006;Cho et al, 2013) reported for recognized species of the genus Nocardioides.…”
Section: Cells Of Strain Pamc 26527mentioning
confidence: 97%
See 1 more Smart Citation
“…¡96.3 %) with recognized species of the genus Nocardioides and the phylogenetic position of strain PAMC 26527 T showed that the strain could be assigned to a novel species in the genus Nocardioides. The DNA G+C content of strain PAMC 26527 T was 69.3 mol%, within the range (67-75 mol%; Prauser, 1976;Yoon et al, 2006;Cho et al, 2013) reported for recognized species of the genus Nocardioides.…”
Section: Cells Of Strain Pamc 26527mentioning
confidence: 97%
“…Most species of the genus Nocardioides have been isolated from non-saline environments, including herbage, oil shale column, groundwater, organisms from freshwater and soil (Collins et al, 1994;Yoon et al, 1997Yoon et al, , 2004Tó th et al, 2008;Lee et al, 2012). However, 11 species have been discovered from various marine environments: Nocardioides marinus (Choi et al, 2007) and Nocardioides marinquilinus (Cho et al, 2013) from seawater, Nocardioides salarius from seawater enriched with zooplankton, Nocardioides marinisabuli , Nocardioides furvisabuli (Lee, 2007), Nocardioides hwasunensis (Lee et al, 2008), Nocardioides dokdonensis (Park et al, 2008) and Nocardioides basaltis (Kim et al, 2009) from beach sand, Nocardioides caricicola (Song et al, 2011) from a halophyte growing on a sand dune, and Nocardioides aestuarii (Yi & Chun, 2004a) and Nocardioides ganghwensis (Yi & Chun, 2004b) from tidal flat sediment.…”
mentioning
confidence: 99%
“…S5) consisted of diphosphatidylglycerol (DPG), phosphatidylglycerol (PG), three unidentified phospholipids (PL1-3), one unidentified glycolipid (GL, missing in strain 4053) and one unidentified lipid (L). DPG was a major polar lipid in the isolates but absent in N. plantarum DSM 11054 T [38]; the existence of PE in N. litoris DSM 103718 T [39] and PI in N. rubriscoriae DSM 23986 T [40] was in contrast to strains S-1144 T lactose, l-arabitol, l-fucose, l-sorbose, l-xylose, maltose, melezitose, melibiose, methyl αd-glucopyranoside, methyl β-d-xylopyranoside, N-acetylglucosamine, raffinose, salicin or starch. In the API 20NE strip, weakly positive for aesculin ferric citrate hydrolysis but negative for gelatin hydrolysis, nitrate reduction, indole production and urease activity.…”
mentioning
confidence: 92%
“…net/ nocardioides. html), which have been isolated from various sources, such as soil [2][3][4][5], seawater [6], desert [7], plants [8][9][10], lake [11] and animals [12]. In our previous studies, several novel species of the order Actinomycetales have been isolated from wild animals (Tibetan antelope, vultures and plateau pika) from the Qinghai-Tibet Plateau, including Nocardioides houyundeii [13], Actinomyces gaoshouyii [14], Actinomyces tangfeifanii [15] and Actinomyces vulturis [16].…”
mentioning
confidence: 99%